DEVELOPING LANGUAGE SKILLS USING AUTHENTIC MATERIALS - Petrosyan.N.V; Misirov Asadbek Amirqul o‘g‘li; Ne‘matov Lazizbek Qo‘chqorboy o‘g‘li (TADQIQOTLAR, 2026)
Abstract. This article scientifically analyzes the role, importance and effectiveness of using authentic materials in the language teaching process. Authentic texts, audio and video resources are considered as important tools in developing students’ listening comprehension, reading, writing and speaking skills. The article covers the types of authentic materials, methods of integrating them into the teaching process, their advantages and problems encountered. It also provides practical recommendations on creating real communicative situations in language teaching, increasing cultural competence and increasing students’ motivation. Keywords: authentic materials, language skills, communicative approach, listening comprehension, reading skills, writing skills, speaking skills, authentic texts, cultural competence, methodology, innovative approach.